Application of Virtual Laboratory (PhET) Learning Media to Students' Scientific Literacy Skills at Junior High Schools - Putri Pratiwi Abada; Tirtawaty Abdjul; Nurhayati Nurhayati; Abdul Haris Odja; Muhamad Yusuf (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
21st-century learning demands that students possess critical thinking, creative, and problem-solving skills based on science literacy. However, observations at SMP Negeri 3 Kabila and SMP Negeri 1 Tapa indicate that science learning remains dominated by lecture methods and limited laboratory facilities, resulting in low process skills and student science literacy. This study aims to analyze the effect of implementing the PhET virtual laboratory learning media integrated with the Problem-Based Learning (PBL) model on students' science literacy skills regarding the topic of matter and its changes. This study uses a quantitative approach with a one-group pretest–posttest design, combined with a multi-site, replicated-treatment design. The research sample consisted of 112 seventh-grade students, selected via cluster sampling from two schools: SMP Negeri 3 Kabila and SMP Negeri 1 Tapa. The research instrument consisted of a science literacy test with 10 items that measured the ability to explain scientific phenomena, evaluate scientific investigations, and interpret scientific data. Data analysis used the Kolmogorov-Smirnov normality test, paired t-test (hypothesis test), and N-Gain calculation. The research results showed that the data were normally distributed and that the use of the PhET virtual laboratory media had a significant effect on students' science literacy skills, as indicated by t-values ≥ t-table in all classes. The improvement in skills was also reinforced by the N-Gain value in the moderate category. This shows that PhET-based learning is effective in improving students' science literacy. So, it can be concluded that integrating the PhET virtual laboratory with the PBL model has a positive impact on students' science literacy skills in the topic of matter and its changes and can serve as an alternative learning medium in schools with limited laboratory facilities.